METHODOLOGICAL APPROACHES TO THE STUDY OF THE RELATIONSHIP BETWEEN MORALITY AND LAW: IN THE CONTEXT OF SOCIO-SPIRITUAL STABILITY - Saitmurodov , Jobirjon (Oriental Journal of History, Politics and Law, 2026)
The article provides a methodological analysis of the relationship between morality and law in the context of socio-spiritual stability. It attempts to substantiate that, although morality and law are independent normative systems, they are functionally and task-wise close to each other in social life. The role of both systems in regulating human behavior, forming responsibility, strengthening the criteria of justice, exercising social control, as well as ensuring trust, solidarity and legality in society, is comparatively analyzed on the basis of ethical-political, Eastern-Muslim philosophical, normative-legal, sociological and integrative approaches.